2004
DOI: 10.1111/j.1440-1746.2004.03360.x
|View full text |Cite
|
Sign up to set email alerts
|

High viral load is a risk factor for hepatocellular carcinoma in patients with chronic hepatitis B virus infection

Abstract: The present findings indicate that high viral load is a risk factor for HCC in patients with chronic HBV infection. Patients with a high HBV viral load should be carefully monitored for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 40 publications
4
57
0
Order By: Relevance
“…Our findings are partly consistent with studies in different areas. In Japan, Ohata et al [25] have investigated the risk factors for HCC in 73 patients with HBV-associated liver disease. A high viral load of HBV DNA, together with age and histological fibrosis, were found to be linked to the occurrence of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are partly consistent with studies in different areas. In Japan, Ohata et al [25] have investigated the risk factors for HCC in 73 patients with HBV-associated liver disease. A high viral load of HBV DNA, together with age and histological fibrosis, were found to be linked to the occurrence of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Further, none of the six patients in the inactive replication group developed end stage liver diseases such as cirrhosis and hepatocellular carcinoma after the follow-up period, while 4 of the 18 patients in the active replication group developed them (data not shown). High viral load, which is usually associated with active hepatitis, has been reported to be a risk factor for development of hepatocellular carcinoma even in patients with chronic hepatitis B who achieved HBe antigen seroconversion [Ikeda et al, 2003;Ohata et al, 2004]. We could not compare long-term prognosis between patients in the inactive and active replication groups in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…39 Studies have confirmed that high HBV viral load is a major risk factor for the development of HCC in patients with chronic HBV infection and is also a risk factor for recurrence after resection. [40][41][42][43] Recent large prospective studies have confirmed that coffee consumption decreases the risk of liver cancer, 4 4-4 6 however, it has not been determined that coffee drinking really decrease the incidence of HCC. Other risk factors for development of HCC, including obesity and type 2 diabetes, have been described elsewhere.…”
Section: Natural History Of Hccmentioning
confidence: 99%